THE HISTORY, DEVELOPMENT AND IMPORTANCE OF THE UZBEK LANGUAGE - Rahmonova Nigina; Saodat Agzamkhodjaeva (Western European Studies, 2025)
The article explores the history,development,and modern significance of the Uzbek language.Uzbek belongs to the Turkic language family and has ancient roots.It evolved based on the Chagatai language and is now actively used as the state language.The article reveals the different stages of its development and its role in society.
Keywords: Uzbek language; language history; ancient Turkic language